Effects of Ractopamine HCL, L-Carnitine and dried distillers grains with solubles on growth, carcass traits, loin and jowl fat quality of finishing pigs, and energy and protein sources in nursery diets - Ying, Wei (Kansas State University, 2011)
Six experiments using 3,862 pigs were conducted to evaluate effects of ractopamine HCl (RAC) feeding programs, dietary L-Carnitine and dried distillers grains with solubles (DDGS) on growth, carcass traits, loin and jowl fat quality of pigs, and energy and protein sources in nursery diets. In Exp. 1 and 2, RAC-fed pigs had greater (P<0.05) ADG, G:F and HCW compared with the control. Within RAC treatments, there were no differences in growth. Pigs fed step-up RAC had increased (P<0.01) percentage lean, fat-free lean index and loin depth but decreased (P<0.01) backfat than the control or constant treatment. In Exp. 2, pigs fed step-up RAC program had greater (P<0.05) ADG and G:F than the constant treatment. Pigs fed constant RAC had greater (P=0.002) carcass yield than controls. There were no overall differences in other carcass traits among treatments. In Exp. 3, dietary L-Carnitine improved (P<0.02) ADG and final BW. A DDGS × L-Carnitine interaction (quadratic, P<0.01) was observed for G:F. Pigs not fed DDGS had similar G:F, but in DDGS diets pigs fed 50 ppm L-Carnitine had worse G:F than those fed 100 ppm. Pigs fed L-Carnitine had greater (P<0.02) HCW compared with those not fed L-Carnitine. Increasing L-Carnitine up to 100 ppm increased HCW (quadratic, P<0.03) and backfat (quadratic, P<0.04), with the maximum response at 50 ppm dietary L-Carnitine. Increasing L-Carnitine increased (linear, P<0.04) purge loss of loin. Feeding DDGS increased (P<0.001) linoleic acid and iodine value of jowl fat compared with feeding no DDGS. However, feeding L-Carnitine did not change jowl fatty acid composition. In Exp. 4, 5 and 6, nursery pigs fed choice white grease (CWG) had improved (P<0.02) G:F than pigs fed a control diet or an alcohol based energy source. Also, pigs fed CWG had greater (P<0.04) ADG in Exp. 4 and 6 and had reduced (P<0.01) ADFI in Exp. 5. The alcohol based energy source improved (P<0.04) ADG and ADFI with no change in G:F in Exp. 4; but did not affect growth in Exp. 5 and 6. In Exp. 6, pigs fed AV-E Digest had equal performance as nursery pigs fed other specialty proteins.
Keywords: DDGS; Energy; L-Carnitine; Ractopamine HCl; Protein; Pigs; Animal Sciences (0475)